Monetary policy of the National bank of Kazakhstan: chronological analysis and assessment - D. B. Kanagatova; V. N. Sidorenko (Экономика: стратегия и практика)
The article aims to determine the role and place of monetary policy in the economic development of the country. When conducting a chronological analysis, attention is focused on the periods of sharp devaluation of the national currency. A dynamic assessment of changes in the exchange rate against the us dollar was made. The policy of the National Bank in the context of the crisis is consistently analyzed and evaluated. An econometric assessment of the investment function is made to justify the monetary policy instruments used. The model is based on quarterly statistics for the last ten years in Kazakhstan. The authors revealed the necessary conditions for the occurrence of speculative attacks on the currency market. Based on these patterns, three options for the Central Bank’s actions to prevent speculative attacks are proposed. The resulting investment model of Kazakhstan allows concluding that the inflation targeting policy cannot ensure sustainable economic growth. The authors concluded that monetary policy plays an important role in macroeconomic regulation. At the same time, the raw material orientation of the economy imposes restrictions on the use of classical monetary policy instruments.Keywords: economic growth, monetary policy, inflation targeting, investments, speculative attacks, exchangerate.